The psychological pressure of the terrorist casualties at immigration camps - Sanaa Mohamed Farag; Rand Hamid Majeed (Zanco Journal of Humanity Sciences)
The study of psychological pressure on individuals is one of the important topics that occupied the minds of scientists and researchers in the field of psychology, education and various human sciences, because it leaves devastating results in the lives of individuals. Identifying the psychological pressures of terrorism victims in the camps for the displaced. Second, identifying the significance of the differences according to the gender variation. The current research community consisted of terrorism victims in the camps for the displaced (Debagah camp in Kirkuk governorate for the current year (2018-2019). The study sample consisted of (60) displaced victims of terrorism by (30) males and (30) females were They are randomized. Statistical methods were used to extract the results T-test for one sample to measure psychological stress, as well as finding the differences between the arithmetic mean of the scale and the mean. The hypothesis and the final test of two independent samples to find the differences between male and female for the measure of psychological pressure. Where the current research reached the following results that the members of the research sample have psychological pressures, there are significant differences.